77.7k views
1 vote
What is equivalent 3(-5x+2)-7x

User Dmarvs
by
5.2k points

2 Answers

2 votes

Answer:

3(-5x + 2) - 7x = -22x + 6

Explanation:


3(-5x+2)-7x\qquad\text{use the distributive property:}\ a(b+c)=ab+ac\\\\=(3)(-5x)+(3)(2)-7x\\\\=-15x+6-7x\qquad\text{combine like terms}\\\\=(-15x-7x)+6\\\\=-22x+6

User Jijinp
by
5.6k points
6 votes
-22x+6 Because you distribute 3 to get -15x+6-7x then you add -15x and -7x to get -22x+6
User Codable
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.